Fundamentals of randomized clinical trials in wound care: Reporting standards. Issue 5 (12th August 2013) - Brölmann, Fleur E.; Eskes, Anne M.; Sumpio, Bauer E.; Mayer, Dieter O.; Moore, Zena; Ågren, Magnus S.; Hermans, Michel; Cutting, Keith; Legemate, Dink A.; Vermeulen, Hester; Ubbink, Dirk T.
Abstract In wound care research, available high‐level evidence according to the evidence pyramid is rare, and is threatened by a poor study design and reporting. Without comprehensive and transparent reporting, readers will not be able to assess the strengths and limitations of the research performed. Randomized clinical trials (RCTs) are universally acknowledged as the study design of choice for comparing treatment effects. To give high‐level evidence the appreciation it deserves in wound care, we propose a step‐by‐step reporting standard for comprehensive and transparent reporting of RCTs in wound care. Critical reporting issues (e.g., wound care terminology, blinding, predefined outcome measures, and a priori sample size calculation) and wound‐specific barriers (e.g., large diversity of etiologies and comorbidities of patients with wounds) that may prevent uniform implementation of reporting standards in wound care research are addressed in this article. The proposed reporting standards can be used as guidance for authors who write their RCT, as well as for peer reviewers of journals. Endorsement and application of these reporting standards may help achieve a higher standard of evidence and allow meta‐analysis of reported wound care data. The ultimate goal is to help wound care professionals make better decisions for their patients in clinical practice.